2010
DOI: 10.1088/1741-2560/7/1/016009
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between subcortical local field potential oscillations and Parkinsonian resting tremor

Abstract: To study the dynamical mechanism which generates Parkinsonian resting tremor, we apply coupling directionality analysis to local field potentials (LFP) and accelerometer signals recorded in an ensemble of 48 tremor epochs in four Parkinsonian patients with depth electrodes implanted in the ventro-intermediate nucleus of the thalamus (VIM) or the subthalmic nucleus (STN). Apart from the traditional linear Granger causality method we use two nonlinear techniques: phase dynamics modelling and nonlinear Granger ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 114 publications
4
71
0
Order By: Relevance
“…When the tremor occurs, both AR and AR-BEKK models identify the causal influence from brain to tremor. However, the AR-BEKK model also detects a feedback from tremor to brain which has been broadly reported in the literatures (Smirnov et al, 2008;Tass et al, 2010). A significant influence from brain to tremor at around 4 Hz is spotted which is also consistent with the previous findings (Wu et al, 2008).…”
Section: Application To Parkinson Datasupporting
confidence: 89%
“…When the tremor occurs, both AR and AR-BEKK models identify the causal influence from brain to tremor. However, the AR-BEKK model also detects a feedback from tremor to brain which has been broadly reported in the literatures (Smirnov et al, 2008;Tass et al, 2010). A significant influence from brain to tremor at around 4 Hz is spotted which is also consistent with the previous findings (Wu et al, 2008).…”
Section: Application To Parkinson Datasupporting
confidence: 89%
“…Tremor-related theta band oscillations are typically no pronounced feature in LFP recordings, presumably since different neuronal subpopulations belonging to different limbs oscillate with time varying phase and frequency relationships [41,43,44]. Nevertheless, with nonlinear data analysis tools it was shown that theta band (3-7 Hz) LFP oscillations drive the peripheral tremor [45].…”
Section: Resultsmentioning
confidence: 99%
“…Instantaneous phases of oscillating systems appear to be most sensitive to appearance of weak coupling between systems [44,45,[60][61][62]. In this case, with coupling increasing the first changes in system dynamics take place in the phases and only afterwards they can be detected in the amplitudes.…”
Section: Phase Dynamics Analysis For Coupling Systemsmentioning
confidence: 99%